Code-Switching Practices among Bilingual Teachers in MAN 1 Labuhanbatu Utara - Sumarsih (JELIM : Journal of Education, Language, Social and Management, 2025)
This study investigates the code-switching practices of bilingual teachers at MAN 1 Labuhanbatu Utara and explores the pedagogical functions and implications of language alternation in an English as a Foreign Language (EFL) classroom. Through classroom observations, teacher interviews, and student feedback, the research reveals that code-switching is used strategically to support instruction, enhance student comprehension, manage classroom behavior, and build social rapport. The types of code-switching identified include intra-sentential, inter-sentential, and tag-switching, with intra-sentential being the most frequently used. Findings suggest that while most students benefit from code-switching, a careful balance is needed to ensure sufficient exposure to the target language. This study concludes that code-switching, when used intentionally and judiciously, can be a valuable pedagogical tool in bilingual education. It recommends ongoing professional development to help teachers use code-switching effectively and support learners’ language acquisition.